Fall establishment of zoysiagrass on roadsides in the U.S. transition zone. Issue 1 (25th May 2022) - Miller, Grady; Gragg, Ben; Pinnix, Drew; McCauley, Ray; Milla‐Lewis, Susana
Abstract: Vegetation management around roadsides and guardrails is time‐consuming and expensive for a department of transportation. These organizations desire dense vegetation that has slow vertical growth and minimal weed invasion once established, and zoysiagrass ( Zoysia spp.) is a suitable species for this use. The objective of this study was to compare fall versus spring plantings for establishing zoysiagrass on North Carolina roadsides. 'Crowne' (sprigs) and 'Compadre' (sprigs and seed) zoysiagrasses ( Zoysia japonica Steud.) were planted in fall 2017 (September, October, November) and spring 2018 (March, April, May) in Lenoir and Yadkin Counties, NC. Data collection was initiated in summer of 2018 and continued through July 2019. The mean percentage of zoysiagrass cover was recorded individually for each establishment timing and method. Zoysiagrass planted with seed achieved coverage quicker than sprigging for all monthly plantings. In Yadkin, March and May seedings achieved 95 and 98% coverage in September 2018, respectively; whereas Compadre's sprigging coverage was 67%. In Lenoir, seed planted in November 2017 and March 2018 achieved 32 and 35% cover by September 2018, respectively, whereas sprig plantings showed <6% coverage. Coverage was faster for spring‐planted materials, but after one calendar year, fall and spring seed planting had similar coverage. The results from this research suggest that zoysiagrass can be established with minimal inputs in fall as well as spring on North Carolina roadsides. Core Ideas: Seeded zoysiagrass achieved coverage quicker than sprigged zoysiagrass. Zoysiagrass coverage was quicker for spring plantings, but fall plantings were successful. Zoysiagrass can be established on roadsides with minimum inputs.